The Relationship Between Technology Use and Problem Technology Use and Potential Psychosocial Mechanisms: Population-Based Telephone Survey in Community Adults During COVID-19 - Yang, Xue; Yip, Benjamin H. K.; Lee, Eric K. P.; Zhang, Dexing; Wong, Samuel Y. S. (Frontiers in Psychology, 2021)
Background: Although digital technology enables people to stay connected during COVID-19, protracted periods of isolation, crisis-induced stress, and technology-based activity may intensify problem technology use (PTU), such as social media addiction (SMA) and Internet gaming disorder (IGD). Objective: This study aimed to characterize the patterns and levels of SMA and IGD during COVID-19 in the general population of Hong Kong. We also tested the associations between prolonged use of social media/Internet games and SMA/IGD and the mediation effects of psychosocial statuses (i.e., loneliness, boredom, and post-traumatic stress) on these associations. Methods: A population-based random telephone survey was conducted in community adults in May 2020; 658 social media users and 177 Internet gamers were identified. A structured questionnaire, including the Bergen Social Media Addiction Scale, the DSM-5 IGD Symptoms Checklist, the Post-Traumatic Stress Disorder Scale, Multidimensional State Boredom Scale, and the De Jong Gierveld Loneliness Scale, was used. Time spent on social media and Internet games during and before COVID-19 was also asked. Results: There were 66.2%-81.8% increases in time use of social media or Internet games during COVID-19 compared to pre-COVID self-reported information of the participants. The estimated IGD prevalence rate in the gamers based on the sample weighted to the age distribution and gender ratio of the Hong Kong population was 9.7%, higher than that of pre-COVID research. Age, marital status, education levels, time use of social media, COVID-related post-traumatic stress, boredom, and emotional loneliness were significantly associated with SMA, while time spent on Internet games, boredom, and emotional loneliness were significantly associated with IGD. Boredom positively mediated the associations between time spent on social media/Internet games and SMA/IGD, whereas social loneliness negatively mediated the association between time spent on social media and SMA. Conclusions: These findings highlight the concern of prolonged use of digital platforms during COVID-19 and its role as a ‘double-edged sword’ for psychosocial well-being and behavioral health during COVID-19. It also highlights a need to monitor and prevent PTU in the general public. The observed psychosocial mechanisms are modifiable, and can inform the design of evidence-based prevention programs for PTU.